2022
DOI: 10.3389/fimmu.2022.1005582
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound IL-2 improves the expansion, survival, and phenotype of CAR Tregs and confers resistance to calcineurin inhibitors

Abstract: BackgroundRegulatory T cells (Tregs) play an important role in the maintenance of immune homeostasis and the establishment of immune tolerance. Since Tregs do not secrete endogenous IL-2, they are especially dependent on external IL-2. IL-2 deficiency leads to lower Treg numbers, instability of the Treg phenotype and loss of immune regulation. After organ transplantation, patients are treated with calcineurin inhibitors (CNIs), which further limits available IL-2. Application of low-dose IL-2 expands Tregs but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Engineered CD3ε -TruC Tregs may also benefit from other modifications to improve their functionality 9 . In patients immunosuppression, Tregs could be enhanced by gene editing to induce drug resistance 52,53 or providing artificial IL-2 cytokine signals 54,55 . Here, the minimized transgene size enables easier co-delivery of therapeutic transgenes.…”
Section: Discussionmentioning
confidence: 99%
“…Engineered CD3ε -TruC Tregs may also benefit from other modifications to improve their functionality 9 . In patients immunosuppression, Tregs could be enhanced by gene editing to induce drug resistance 52,53 or providing artificial IL-2 cytokine signals 54,55 . Here, the minimized transgene size enables easier co-delivery of therapeutic transgenes.…”
Section: Discussionmentioning
confidence: 99%
“…To address the issue off‐target effects of native IL‐2, many groups have tested IL‐2 engineering strategies or muteins 145,146 to selectively boost Tregs. In a xenoGVHD model, A2‐CAR Tregs engineered with membrane‐bound IL‐2 showed enhanced persistence and stability in vivo 147 . An alternative approach is to utilize an orthogonal receptor‐ligand system, in which an exogenously administered IL‐2 mutein selectively binds an orthogonal receptor expressed on T cells 148 .…”
Section: ‐Beyond: the Advanced Engineering Era And Into The Clinicmentioning
confidence: 99%
“…Although evidence suggests that tacrolimus and Treg therapy can function together, several studies have demonstrated that IL‐2 engineering can be used to overcome any consequences of IL‐2 depletion during tacrolimus treatment. A2‐CAR Tregs expressing a membrane‐bound IL‐2 were better able to survive and function compared to standard A2‐CAR Tregs when coadministered with multiple injections of tacrolimus 147 . Similarly, an orthogonal IL‐2 system enhanced the survival and proliferation of Tregs in mice treated with tacrolimus and helped maintain heart allograft tolerance 149 .…”
Section: ‐Beyond: the Advanced Engineering Era And Into The Clinicmentioning
confidence: 99%
See 2 more Smart Citations